2013 IEEE Power &Amp; Energy Society General Meeting 2013
DOI: 10.1109/pesmg.2013.6672770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wind penetration on power system stability

Abstract: The paper investigates the impact of large scale wind penetration on the inter-area mode damping of a power system. Simulation results using a two-area test system and a representative GB test system are used for the study. Different possible operating scenarios of the systems are generated and a qualitative behavior of the impact is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Compared with FSIG, DFIG is comparatively new and has a more flexible control in active and reactive power, and thus most of research efforts are devoted to the grid connection study of DFIG in recent decade. Various case studies have been implemented to address different aspects of DFIG in affecting the oscillation stability such as integration method [4]- [9], inertia or other sensitivity based approach [10] [12], reactive power/voltage control [13]- [17], operating condition [18], virtual inertia control [19]- [21], additional damping control [22]- [32] and external energy storage system [33] [34].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Compared with FSIG, DFIG is comparatively new and has a more flexible control in active and reactive power, and thus most of research efforts are devoted to the grid connection study of DFIG in recent decade. Various case studies have been implemented to address different aspects of DFIG in affecting the oscillation stability such as integration method [4]- [9], inertia or other sensitivity based approach [10] [12], reactive power/voltage control [13]- [17], operating condition [18], virtual inertia control [19]- [21], additional damping control [22]- [32] and external energy storage system [33] [34].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Most of these studies show that wind integration increases the damping of these oscillations. However, some works show that under certain operating conditions the installation of wind generation can destabilize these modes of oscillation [5,9]. Previous research has shown power electronics interfaced generation to be effective in damping power system oscillations [6,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It can be proved that at (see Appendix B) (9) where is the vector consisted of elements of corresponding to , is the element of corresponding to state variable , the deviation of rotor speed of the SG. Hence at the complex oscillation frequency , the damping torque provided by the DFIG to the generator can be obtained from (8) and (9) to be (10) where denotes the real part of a complex number. Let the sensitivity of the electromechanical oscillation mode of interests to the damping torque coefficient of the SG be (11) From (10) and (11) it can have (12) The procedure of applying the DTA above shows that the impact of dynamic interactions introduced by the DFIG can be estimated as to be .…”
Section: B Estimation Of Impact Of Dynamic Interactions Introduced Bmentioning
confidence: 99%
“…Useful conclusions are presented in [8] and [9] for guiding how increased wind penetration can safely replace conventional generation in the power system. More recently published work in [10] and [11] used real large-scale power systems to examine the system oscillation modes as affected by the CCBGs and DFIGs. An inclusive investigation is carried out in [10] with different system operating scenarios and combinations of the SGs and the DFIGs.…”
mentioning
confidence: 99%
See 1 more Smart Citation